Physical therapy treatment in chronic wounds – the high voltage stimulation and the magnetotherapy - Sztandera, Paulina; Zbyradowski, Jakub (Journal of Education, Health and Sport, 2018)
Introduction and purpose of the work. Wounds which last in the human body longer than 4-8 weeks are regarded as chronic wounds. Healing process in those wounds does not take place. Medical staff of different specialties should be involved to ensure proper efficiency of the wound healing process. The purpose of the study was to analyze the literature of using physical therapy such as the high voltage therapy, the magnethotherapy and the magnetostimulation in the chronic wound healing process. Brief description of the state of the art. The High Voltage Stimulation is used not only for pain treatment but also in different kinds of wounds. The unipolar or dipolar set is applied, and one or two electrical circuits could be used. Under the active electrode, the primer soaked in physiological saline is used and placed on the wound (the size of the primer is matched to the size of the wound). If the dipolar set is used, electrodes are fixed in opposite parts of the wound. The stimulation is induced with current which does not invoke any movement. The magnetotherapy is a kind of physical therapy which uses the magnetic fields of 1-to 10-20 mT and the frequency under 100 Hz. In the magnetostimulation, the magnetic induction amounts from 1 pT to 100 mT, the frequency from 1 to 1000 Hz. Summary (conclusions). All clinical studies showed that different kinds of physical therapy such as the magnetostimulation, the magnetotherapy, and the high voltage therapy accelerate the process of wound healing. Unfortunately, the application of physical therapy in order to improve the wound healing process is still limited.